Resonances in Reverse Vavilov-Cherenkov Radiation Produced by Electron Beam Passage over Periodic Interface - Gerard Granet; Petr Melezhik; Anatoliy Poyedinchuk; Seil Sautbekov; Yuriy Sirenko; Nataliya Yashina (International Journal of Antennas and Propagation)
Resonances in reverse Vavilov-Cherenkov radiation produced by the charged particles beam passage over periodic boundary of dispersive left-handed medium are found out and studied. Analysis and modeling are performed on the base of rigorous mathematical approaches. For the first time, several physical peculiarities owing to these effects are considered in the conditions of possible resonant scattering of electromagnetic waves.